MSMEs Focus on Instagram Account Quality: Key Factors to Prioritize in Instagram Posting - Berto Mulia Wibawa; Ninditya Nareswari (Institut Teknologi Sepuluh Nopember, 2019)
Nowadays, most of MSMEs have a quite good understanding of social mediaand how it works for their business. In Indonesia, Instagram is one of the bestpowerful tools to introduce and market their product instantly. However,social commerce face problems especially in customer trust. It is suspectedcustomers are doubt to the key factors of social media online shop, i.e.:reputation, transaction, communication, safety, information quality,economic feasibility, and word-of-mouth referrals. The purpose of this studyis to test a framework of Instagram account quality model and its impact onMSMEs social media marketing strategy. An online-based questionnaire wasadministered to 271 MSMEs. Furthermore, structural equation modelingwas used to analyze the data. Findings indicated that there are significanteffects of information quality, reputation, safety, communication, andeconomic feasibility on the Instagram account quality construct. Thepractical implications that need to be emphasized on MSMEs is the need todevelop their information quality on Instagram. It is important because it isthe most significant factor towards Instagram account quality in online storeperception. A focus on improving information quality will also help MSMEsto communicate and promote their post to reach more audience andinteraction with potential consumers.